2022
DOI: 10.1002/jbio.202100398
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic basis for comparative photobiomodulation dosing with multiple wavelengths to direct odontoblast differentiation

Abstract: Multiple wavelength devices are now available for photobiomodulation (PBM) treatments, but their dosimetry for individual or combinatorial use remains unclear. The present work investigated the effects of 447, 532, 658, 810, 980 and 1064 nm wavelengths on odontoblast differentiation at 10 mW/cm2 using either equal treatment time for conventional fluence (300 seconds for 3 J/cm2) or varying times to adjust for individual wavelength photon fluence (4.6 p.J/cm2). Both 447 and 810 nm significantly increased alkali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The ‘ one-size-fits-all ’ protocols or ‘ point-and-shoot ’ approach should no longer be acceptable for PBM treatments for its broad range of clinical applications. Rationalized dosimetry, including individual wavelength photon energy (photonic fluence), appropriate delivery technique, and clinical judgment of targeted biological responses are essential for optimal clinical therapeutic outcomes ( 62 , 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ‘ one-size-fits-all ’ protocols or ‘ point-and-shoot ’ approach should no longer be acceptable for PBM treatments for its broad range of clinical applications. Rationalized dosimetry, including individual wavelength photon energy (photonic fluence), appropriate delivery technique, and clinical judgment of targeted biological responses are essential for optimal clinical therapeutic outcomes ( 62 , 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mice were randomly divided into four groups: (1) AC8 mice without any treatment/controls (AC group; n = 7); (2) AC8 mice treated with PBM (AC + T group; n = 8); (3) wild‐type mice without any treatment/controls (WT group; n = 9); and (4) wild‐type mice treated with PBM (WT + T group; n = 8). Mice in AC + T and WT + T groups received near‐infrared LED light exposure at 25 mW/cm 2 for 120 s at 850 nm for 1 Einstein (4.5 p.J/cm 2 photonic fluence or the conventional dose of 3 J/cm 2 ) for 5 days per week 23 . Mice were placed under a LED light source (Bio900, Platinum LED Inc) at a fixed distance in their original cages without cage covers, and light irradiance was calibrated using an optical power meter (ThorLabs Inc).…”
Section: Methodsmentioning
confidence: 99%
“…Mice in AC + T and WT + T groups received near-infrared LED light exposure at 25 mW/cm 2 for 120 s at 850 nm for 1 Einstein (4.5 p.J/cm 2 photonic fluence or the conventional dose of 3 J/cm 2 ) for 5 days per week. 23 Mice were placed under a LED light source (Bio900, Platinum LED Inc) at a fixed distance in their original cages without cage covers, and light irradiance was calibrated using an optical power meter (ThorLabs Inc). The mice were subjected to a whole-body treatment while they were awake and freely moving in their cage.…”
Section: Photobiomodulation Therapymentioning
confidence: 99%
“…PBM dosimetry has raised significant interest in recent years, primarily due to its efficacy in a broad range of clinical applications, regardless of the underlying pathology and varying protocols. But since Mester's first description of its benefits, PBM has been used rather empirically as a magic wand, without actual knowledge of photobiological, molecular, and intercellular mechanisms of laser-tissue interaction that cannot be ignored [51]. The absence of clear guides for standardizing protocols description and data presentation remains an issue that can limit comparison among studies and the creation of coherent clinical practice guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers emerged in the literature regarding the possibility of enabling comparisons between protocols, creating a system of "dosing consistency, " which is effective with multiple combined wavelengths. Young et al suggested using the terms photonic fluence (p.J/cm 2 ) and "Einstein" (photonic fluence at 810 nm as a reference wavelength) [51]. This enables easy, universal interoperability between dose recommendations with different wavelengths.…”
Section: Discussionmentioning
confidence: 99%